2012
DOI: 10.3892/ol.2012.836
|View full text |Cite
|
Sign up to set email alerts
|

Two consecutive days of treatment with liposomal cisplatin in non-small cell lung cancer

Abstract: Abstract. Liposomal cisplatin (Lipoplatin) is a new agent, a cisplatin formulation that has been investigated in a number of studies and compared with cisplatin with respect to toxicity and effectiveness. It has been administered once weekly and in combination with a second agent, once every two weeks. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A macromolecular formulation of cisplatin, termed lipoplatin, that appears to selectively accumulate in the tumor environment [3] is also progressing through clinical trials and could lead to more selective treatments with reduced side-effects [4]. Many other types of macromolecular systems are also under development [5].…”
Section: Page 6 Of 100mentioning
confidence: 99%
“…A macromolecular formulation of cisplatin, termed lipoplatin, that appears to selectively accumulate in the tumor environment [3] is also progressing through clinical trials and could lead to more selective treatments with reduced side-effects [4]. Many other types of macromolecular systems are also under development [5].…”
Section: Page 6 Of 100mentioning
confidence: 99%
“…As this liposomal formulation is less toxic, preclinical and clinical studies made on NSCLC have shown that a 3-6 times higher dose than the standard dose of cisplatin resulted to a better anticancer effect with lower toxicity [24,25]. In our studies, no toxicity was observed with Lipoplatin ™ as measured by the mean survival time of the animals compared to controls, whatever the route of administration used.…”
Section: Discussionmentioning
confidence: 40%
“…One successful example is the liposomal formation (e. g. SPI‐77, [6] Lipoplatin, [7] LiPlaCis [8] ) of cisplatin within nano‐sized hydrophilic bilayers of phospholipids [8a,9] . Liposomal encapsulation enhances the circulation time of the drug, leading to increased drug accumulation at the tumor site through the enhanced permeability and retention (EPR) effect with a simultaneous reduction of adverse side effects [7a,8a,9] …”
Section: Introductionmentioning
confidence: 99%